VECTOR AUTOREGRESSION (VAR) ANALYSIS OF THE NEXUS BETWEEN EXCHANGE RATE VOLATILITY AND PRIVATE DOMESTIC CONSUMPTION IN NIGERIA. (December 2019) - Chukwuma, Johnbosco; Ezekwe, Ezekwe; Ifeanyi, Christopher; Morris, Morris; EloOghene, Rachael
No abstract available